Optical nonlinear refractive index study by Z-scan technique of GOQDS dispersed in an aqueous solution - Gutiérrez-Fuentes, R.; Jiménez-Pérez, J. L.; García-Vidal, O. U.; Luna-Sánchez, J. L.; Correa-Pacheco, Z. N.; Sánchez-Ramírez, J. F.; Algatti, M. A. [UNESP]; Ozaki, J. (Springer Nature, 2024)
In this work, electrospun polyacrylonitrile nanofibers (PAN), wheat, and orange powders obtained by dehydration and carbonization were used as precursors to prepare colloidal suspensions of graphene oxide quantum dots (GOQDs). Different concentrations and centrifugation speeds of 8000 to 12,000 rpm of GOQDs in distiller water were employed. Nonlinear optical properties of the GOQDs were measured by the Z-scan technique. For the experimental, a laser of continuous wavelength of 325 nm was used as an excitation source. The excitation beam was focused using a lens of 10 cm and the sample was moved across the focal region along the Z-axis. It was shown that the concentration of GOQDs highly improved the nonlinear optical properties of the sample. The morphology and structure of GOQDs were evaluated by transmission electron microscopy (TEM) and UV–vis spectroscopy, respectively. From the experimental results, the optical nonlinear refractive index of the GOQDs were obtained, with values of −4.51 × 10–9 cm2/W and −5.83 × 10–9 cm2/W for 8000 a 12,000 rpm for PAN, −2.97 × 10–9 and −3.04 × 10–9 cm2/W for 8000 a 12,000 rpm for wheat, and −3.45 × 10–9 and −3.63 × 10−9cm2/W for 8000 to 12,000 rpm for orange, respectively. This suggests that GOQDs aqueous solution could be a very promising nonlinear medium, establishing the bases of nonlinear photonics and bio-imaging for optoelectronic applications.